2014
DOI: 10.1534/genetics.114.170258
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Mutation Rates Show a Sigmoidal and Saturable Increase Due to the RpoS Sigma Factor in Escherichia coli

Abstract: Stress-induced mutagenesis was investigated in the absence of selection for growth fitness by using synthetic biology to control perceived environmental stress in Escherichia coli. We find that controlled intracellular RpoS dosage is central to a sigmoidal, saturable three-to fourfold increase in mutation rates and associated changes in DNA repair proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Recently, the Ferenci laboratory showed that varying RpoS levels gives rise to different mutation rates and patterns. Increasing the levels of RpoS leads to a decrease of MutS levels and an increase of DNAP IV levels and vice versa [ 90 , 92 , 93 ]. These observations are highly relevant for the isolation of strains with improved protein production characteristics, since, during their isolation, cells are exposed to stress caused by the production of proteins.…”
Section: Dna Integrity and Mutagenesismentioning
confidence: 99%
“…Recently, the Ferenci laboratory showed that varying RpoS levels gives rise to different mutation rates and patterns. Increasing the levels of RpoS leads to a decrease of MutS levels and an increase of DNAP IV levels and vice versa [ 90 , 92 , 93 ]. These observations are highly relevant for the isolation of strains with improved protein production characteristics, since, during their isolation, cells are exposed to stress caused by the production of proteins.…”
Section: Dna Integrity and Mutagenesismentioning
confidence: 99%
“…The ability to measure mutation rates at fixed growth rates allows one to test some of the core assumptions on the environment-mutation relationship. One common notion in studies of SIM is the regulatory requirement for RpoS (Lombardo et al, 2004;Storvik and Foster, 2010;Maharjan and Ferenci, 2014). Essentially all external stresses induce elevated levels of RpoS, as does stationary phase and reduced growth rate (Notley-McRobb et al, 2002;Hengge, 2011).…”
Section: Correlation Of Mutation Rates With the General Stress Responmentioning
confidence: 99%
“…In this century, however, the MES assumption of mutational randomness and unchanging mutation rates has been challenged (Yampolsky and Stoltzfus, ; Ninio, ; Fitzgerald and Rosenberg, ). A factor in the changing views on the role of environments in mutation rates was the emerging evidence for stress‐induced mutagenesis (SIM), mainly using Escherichia coli as the model organism (Foster, ; Galhardo et al ., ; Rosenberg et al ., ; Maharjan and Ferenci, , ).…”
Section: Introduction To the Stress–mutation Relationshipmentioning
confidence: 99%
“…Like amplification within the F , the higher copy number increases the number of targets and would lead to an elevated revertant frequency. Other recent studies have argued in favor of stress mutagenesis by showing that mutation rates can be elevated threefold to fourfold without selection for growth fitness by controlling the intracellular concentration of the transcription factor RpoS [31], which had earlier been reported to be required for adaptive stress mutagenesis [21]. Thus, the debate continues owing to the difficulty of cleanly differentiating whether the elevated revertant frequencies observed after long incubation on selective media are ascribable to stress-induced mutagenesis [19,32] that may involve error-prone DNA synthesis during recombination in nongrowing cells [33] or to the growth limitation serving exclusively as a selective agent for revertants that arise at conventional mutation rates [30,[34][35][36].…”
Section: Tablementioning
confidence: 99%